The Gallery Walk Method On Students' Critical Thinking Skills In Biology Lessons For Class X - Zul Andry Saputra; Saptiawati Saptiawati; Ceni Liswati; Margareta Ayu W; Andri Suryana (STABN RADEN WIJAYA WONOGIRI, 2023)
Critical thinking is a fundamental competency in Biology education ; however , classroom instruction in many schools remains dominated by conventional approaches that limit student engagement and hinder the optimal development of higher -order thinking skills . This study aimed to examine the effect of the Gallery Walk learning method on students ' critical thinking skills in Grade X Biology at SMAN 12 Kota Bekasi. A quantitative approach employing a quasi-experimental nonequivalent control group design was applied . The research sample consisted of 80 students , divided equally into an experimental group and a control group . Critical thinking ability was measured using a validated test administered as both pre-test and post-test . Data analysis was conducted using the Wilcoxon Signed Rank Test to identify within-group improvement and the Mann –Whitney U Test to examine differences between groups , as the data were not normally distributed . The findings revealed statistically significant improvement in critical thinking skills among students in the experimental group following the implementation of the Gallery Walk method (p < 0.05). Furthermore , the Mann –Whitney U Test indicated a significant difference in critical thinking performance between the experimental and control groups (p < 0.05), with the experimental group demonstrating a higher mean rank . These results indicate that the Gallery Walk method has a positive and significant effect on enhancing students ' critical thinking skills in biology learning.